Switched-capacitorized DC/DC converters - Lee, Yeow Boon. (2009)
This Electrical and Electronic Engineering (EEE) final year project(FYP) report will involve a new type of DC/DC converter circuitry that has never been created before. This new type of DC/DC converter is called switched-capacitorized DC/DC converter. It uses only capacitors to achieve voltage-lift, which makes it capable of increasing the voltage output tremendously. Since it does not use any inductor and also requires less electrical components, it will have a small size yet having high power density. Power losses and electromagnetic interference will also be low as no inductor is involved. Also, the high efficiency of power transfer and high voltage gain will be of great interest if it is indeed achievable. This switched-capacitorized DC/DC converter can only operate in Discontinuous Input Current Mode (DICM). The switched capacitors will be charged to the DC source voltage during the switch-off period, and during the switch-on period, the switched capacitors will join in the converter circuit together with the source voltage to produce a higher input voltage to the circuit. This design can be used on any DICM DC/DC converter circuit to boost the input voltage. The author will use this new circuitry to test on existing DICM DC/DC converters and record down the resulting voltage-lift and its efficiency. The simulation results have been achieved using software simulation programme ‘PSIM’ and 8 types of common DICM DC/DC converter circuits have been used in the simulation.